Guyana : Housing Market and Implications for Macroprudential Policies - Chow, Julian (IMF Working Papers; Working Paper ;, 2020)
Guyana's residential real estate prices have been rising, particularly in the capital city Georgetown, following the discovery of oil in 2015. In line with the growing demand for housing, commercial banks' housing loans have increased, prompting higher household debt. This paper presents two analyses which suggest that housing prices in Georgetown and banks' lending to the housing sector appear to be in their early stages of growth. However, given the data limitations and caveats that underpin the analyses, the findings could also indicate early signals of possible risks. Further data collection would support surveillance and deeper studies. At the same time, enhancing prudential measures would help safeguard financial and macroeconomic stability. These include strengthening the monitoring of the housing market, bank lending practices and household debt, as well as fortifying the macroprudential framework, including with more effective toolkits for early intervention.